Consumer Legal Protection in Fintech Lending Against the Risk of Default - Rahmat Budiyanto Hiola; Mutia Ch. Thalib; Sri Nanang Meiske Kamba (The Easta Journal Law and Human Rights, 2026)
The rapid growth of financial technology lending (fintech lending) in Indonesia has increased public access to digital financing but has also created legal problems related to consumer protection against default risks. Consumers frequently face unlawful debt collection practices, misuse of personal data, lack of transparency in loan terms, and legal uncertainty caused by illegal fintech lending platforms. Although various studies have discussed fintech legality and consumer protection, limited research has specifically examined the effectiveness of legal protection against default-related risks and the responsibility of fintech lending providers. This study aims to analyze consumer legal protection in fintech lending services and evaluate the responsibility of providers in safeguarding consumer rights. The research employs a normative legal method using statutory and conceptual approaches. Data were collected through a literature review of legislation, legal doctrines, and scholarly publications concerning consumer protection and fintech lending. The findings indicate that existing regulations, including consumer protection, personal data protection, and fintech lending regulations, have not been fully effective due to weak supervision of illegal platforms, inadequate enforcement of personal data protection provisions, and persistent abusive debt collection practices. The study concludes that fintech lending providers must ensure transparency, data security, and ethical collection procedures. Strengthening regulatory supervision, improving coordination between relevant regulations, and imposing stricter sanctions on illegal operators are necessary to enhance consumer protection and create a secure and sustainable digital financial ecosystem.